Peran Konten TikTok sebagai Media Komunikasi Pemasaran dalam Membangun Brand Awareness PT Asia Jaya Timbangan Palembang - Yesi Amelia; Eraskaita Ginting (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
The development of social media platforms has changed the way companies engage with their audiences. TikTok, a short video platform, has become an important venue for various sectors, such as PT Asia Jaya Timbangan Palembang. This study aims to analyze the role of TikTok content as a marketing communication tool in increasing brand awareness. Using a qualitative descriptive approach, this article illustrates that the use of educational, demonstrative, and interactive content successfully attracts the audience's attention, interest, and memory of the brand. The results of the study show that TikTok not only functions as a place of entertainment but also as an effective marketing tool for building brand awareness in the digital age